Protein Purification - Ahmad, Rizwan (IntechOpen, 2012)
The current volume entitled Protein Purification is designed to facilitate rapid access to valuable information about various methodologies. It aims as well to provide an overview of state-of-art techniques for the purification, analysis and quantification of proteins in complex samples using different enrichment strategies.